2008
DOI: 10.1039/b803147a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–deuterium exchange experiments to probe the decomposition reaction of sodium alanate

Abstract: NaAlH(4) is the archetypical complex hydride for hydrogen storage. The extraordinary effect of dopants on the sorption kinetics triggered the investigation of this empirical finding. In this paper, a short review of the state of the art is given. To gain further understanding of the mechanisms involved we label the interacting species during the sorption process. This was experimentally realized by hydrogen-deuterium exchange measurements during the decomposition of NaAlH(4) followed by thermogravimetry, Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 53 publications
9
65
2
Order By: Relevance
“…We note that our calculated results disagree with the findings of Ref. 57 in NaAlH 4 , who found that the low-frequency modes disappeared above the melting point, whereas we find that they remain. This disagreement could be due to our use of periodic boundary conditions in a cell that is very small relative to the particle size in an experimental sample.…”
contrasting
confidence: 57%
“…We note that our calculated results disagree with the findings of Ref. 57 in NaAlH 4 , who found that the low-frequency modes disappeared above the melting point, whereas we find that they remain. This disagreement could be due to our use of periodic boundary conditions in a cell that is very small relative to the particle size in an experimental sample.…”
contrasting
confidence: 57%
“…The mechanochemical synthesis of other new borohydrides in the system ZnCl 2 -MBH 4 , e.g. NaZn 2 (BH 4 ) 5 , proceeds via more complex chemical reactions during ball milling-possibly a combination of metathesis and addition reactions [18,19]. Surprisingly, these observations suggest that ball milling may lead to a state of chemical equilibrium rather than just a statistical distribution of reactants as expected, e.g.…”
Section: )Cl 2 ]mentioning
confidence: 43%
“…However, the interactions of the hydrogen molecules or atoms with solid materials or surfaces are not well known on an atomic level in complex hydrides. The identification of the decomposition reaction pathways of several complex hydrides, the determination of the intermediate species in dehydrogenation reactions, the emission of side products and the role of catalysts are all challenges [5] that require the most advanced characterization instruments and a profound knowledge of the chemical physics of gas-solid interactions. The International Energy Agency (IEA) Task 32 ''H 2 -Based Energy Storage'' addresses hydrogen-based energy storage by developing reversible or regenerative hydrogen storage materials.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the sorption reaction is only reversible under technically applicable conditions, if the material is doped with transition-metal compounds, most efficiently with titanium compounds [68][69][70]. A multitude of experimental and theoretical methods have been applied to unravel the mechanism of the formation and decomposition process of NaAlH 4 -so far without a conclusive model [71][72][73][74][75][76][77][78][79][80][81]. Furthermore, similar effective additives for other complex hydrides e.g.…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%